UNCOVERING RESISTANCE TO ICT USE IN LANGUAGE INSTRUCTION - Nur Kamilah; Mirjam Anugerahwati; Sintha Tresnadewi (Graduate School of Universitas Negeri Malang, 2016)
This article reports a case study that explored a teacher of a high school in Situbondo who is resistant to ICT integration in language instruction. The study started from the concern of a teacher who chose to resist ICT despite the importance and potentials of it in improving learner’s language skill. The study found that the variable of age has influenced other variables like the motivation to learn and the capability to operate ICT for teaching which lead to the preference of resisting and thus he keeps using the conventional teaching method. This variable is not thought to be the only influence to the resistance because it was further found that the teacher’s failure to fulfill the demand of his profession becomes more contributing to it. Therefore, it is suggested that English teachers are aware of the demands of their profession in order to stay on the track of professional teachers.Penelitian ini memaparkan hasil studi kasus terhadap seorang guru bahasa Inggris SMA di Situbondo yang resistan untuk menggunakan TIK di kelas. Berawal dari keprihatinan terhadap guru yang memilih untuk abai terhadap penggunaan TIK, terlepas dari penting dan berpotensinya TIK tersebut dalam meningkatkan keterampilan berbahasa siswa. Ditemukan bahwa variabel usia yang lanjut menjadi penyebab munculnya variabel lain seperti kurangnya motivasi belajar TIK dan rendahnya kemampuan menggunakannya yang berujung pada pilihannya untuk tidak menggunakan TIK di kelas sehingga tetap menggunakan metode mengajar konvensional. Variabel usia tersebut ternyata bukanlah pemicu utama sikap resistan tersebut, melainkan lemahnya kemampuan guru dalam memahami dan memenuhi tuntutan profesinya sebagai guru bahasa Inggris. Oleh karenanya, saran penelitian ditujukan pada guru agar lebih siap terhadap tuntutan dan tantangan lain dalam profesinya sehingga menjadi guru profesional.